The wonder of us - Culbertson, Kim A. (Point, 2017)
Riya and Abby were best friends in their small California town, but Riya and her family moved to Berlin for Riya's junior year and it was hard to stay in touch; so now that the year has passed, Riya proposes that they take a two week Grand Tour and travel around Europe to reconnect--but the trouble is that they have both been hiding secrets, and those secrets threaten to push them apart forever.